Relação entre perfil glicêmico da dieta, excesso de peso e adiposidade em crianças da cidade de Diamantina-MG - Kellen Crisine Silva (2011)
Background: Overweight children has grown exponentially becoming apublic health problem worldwide. Observational studies suggest that diets with high glycemic index daily (GID) and high glycemic load daily (GLD) may increase the risk for the development of this nutritional disorder. Objectives: To describe and critically analyze published studies that investigated IGD and CGD children's diet and it association with overweight, and investigate whether these parameters are risk factor for overweight and adiposity among children age five the city of Diamantina. Methods: A literature review was conducted between the years 1981 to 2011 in different databases (Lilacs, PubMed and Scielo), where articles were sought regarding this matter. It is cross-sectional study nested in a cohort born between 2004 and 2005 in the city of Diamantina / MG. Overweight was measured by body mass index (BMI) and body fat by triceps skinfold thickness (TSF) and subscapular (SST). The GID and GLD were evaluated by a food frequency questionnaire modified consumer (FFQMC). We used logistic Poisson regression and adopted hierarchical model. In univariate analysis we considered the variables that presented p <0.2 as a possible confounding variable of interest, and in multivariate analysis considered variables with p 0.05 as risk factors for overweight. Results: We identified eight observational and four experimental studies in the literature involving quality of carbohydrates diet and risk for overweight in childhood. The prevalence of overweight was 17.23% for the BMI, and high body fat 4.76% by TSFand 7.35% by SST. The average GID was 52.7 (± 4.01) and GLD was 109.0 (± 43.81), the prevalence of inadequate diet was 28% and 74% respectively.There was not difference in fiber intake between the groups appropriate and inappropriate for both the GID and for GLD. After adjusting for potential confounders, GID and GLD did not constitute a risk factor for overweight in childhood. Conclusion: In this study there was no association between dietary glycemic profile and risk for overweight and adiposity in children atfive years old.